Design and Development of Potato Harvesting Equipment (solanum tuberosum l.) for Harvesting Efficiency - Wahyu Anwar; Aprilian Firmansyah (Agriculture Journal, 2025)
Potato (Solanum tuberosum L.) is a high-value horticultural crop in Indonesia; however, harvesting is still predominantly conducted manually, resulting in low efficiency, high labor demand, and a high risk of tuber damage. This study aimed to design, develop, and evaluate a semi-mechanical potato harvesting machine suitable for field conditions in Indonesia. The research stages included field observation, computer-aided design (CAD), prototype fabrication, and field performance testing on three planting beds. The parameters evaluated were effective working capacity, harvesting efficiency, and tuber damage percentage. The developed harvester achieved an average effective working capacity of 240.60 Kg/Hour or 0.0118 ha/hour, with a tool efficiency of 65.74%. The average tuber damage was 5.96%, indicating good harvesting quality. These results demonstrate that the developed harvester significantly improves harvesting productivity and reduces yield losses compared to manual methods. Further improvements are recommended, particularly regarding blade-angle adjustment and collection system optimization.